(untitled) (GAIMS Journal of Medical Sciences, 2024)
Coinfection with Dengue fever and Scrub Typhus presents significant diagnostic and therapeutic challenges, particularly in pediatric cases. We report a 6-year-old girl with fever, headache, maculopapular rash, and a vesicular lesion on the knee that progressed to a black eschar. She developed generalized edema, oral bleeding, decreased urine output, and renal dysfunction. Laboratory tests revealed anemia, leukocytosis, thrombocytopenia, elevated serum urea and creatinine, hypoalbuminemia, and hyponatremia. The Weil-Felix test was positive for OXK titer 1:320, and Dengue IgM antibodies were detected, complicating the diagnosis. Treatment with doxycycline, azithromycin, and local care for the eschar led to clinical improvement. This case highlights the importance of considering coinfection in febrile illnesses and emphasizes the need for accurate and timely diagnosis for effective management.